# How do you solve #4-4 + log _ 9 (3x - 7) = 6#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve (4 - 4 + \log_9(3x - 7) = 6):

- Combine like terms on the left side of the equation.

[4 - 4 = 0]

[0 + \log_9(3x - 7) = 6]

- Subtract 6 from both sides of the equation.

[\log_9(3x - 7) = 6 - 6]

[\log_9(3x - 7) = 0]

- Rewrite the equation in exponential form.

[9^0 = 3x - 7]

- Simplify (9^0), which equals 1.

[1 = 3x - 7]

- Add 7 to both sides of the equation.

[1 + 7 = 3x - 7 + 7]

[8 = 3x]

- Divide both sides by 3.

[x = \frac{8}{3}]

So, the solution to the equation is (x = \frac{8}{3}).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7